2012
DOI: 10.1111/j.1464-410x.2012.11402.x
|View full text |Cite
|
Sign up to set email alerts
|

Choice between prostatectomy and radiotherapy when men are eligible for both: a randomized controlled trial of usual care vs decision aid

Abstract: Trial NTR1334What's known on the subject? and What does the study add?• Many patients are eligible for more than one treatment option for prostate cancer. In usual care, urologists have a large influence on the treatment choice. Decision aids, providing balanced information on the pros and cons of different treatment options, improve the match between patient preferences and treatment received.• In men eligible for both surgery and external beam radiotherapy, treatment choice differed by hospital. Across the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 47 publications
(43 reference statements)
3
68
0
Order By: Relevance
“…Previous studies among men with prostate cancer have demonstrated patient preferences for various treatment options for prostate cancer (e.g. active surveillance, surgery, radiation, or hormonal therapy) [1719], cosmetic results of different types of prostatectomies [20] and on functional outcomes (erectile function and continence) [21]. Our results expand on this pre-existing body of work, and demonstrate that patient preferences indeed induce a demand for greater utilization of healthcare services, which could feasibly impact the overall burden of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies among men with prostate cancer have demonstrated patient preferences for various treatment options for prostate cancer (e.g. active surveillance, surgery, radiation, or hormonal therapy) [1719], cosmetic results of different types of prostatectomies [20] and on functional outcomes (erectile function and continence) [21]. Our results expand on this pre-existing body of work, and demonstrate that patient preferences indeed induce a demand for greater utilization of healthcare services, which could feasibly impact the overall burden of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen unique DAs were identified across the 23 studies. The majority of studies reported on a single patient-clinician interaction (n=18, 78%); only three studies (13%) [38,59,72] reported more than one patientclinician interaction. In two studies (9%), [70,73] it was not possible to determine the number of patient-clinician interactions (Table 1).…”
Section: Overview Of Studiesmentioning
confidence: 99%
“…[76] Qualitatively, as the number of SDM elements in each study increased, there was no corresponding increased likelihood of effectiveness (statistical significance) in terms of study outcomes (Table 3). Of note, two studies [61,72] were classified as highly effective, and both of those studies only assessed a single outcome: treatment decision differences between groups after exposure to a DA. In both studies, [61,72] exposure to a DA led to "better" treatment choice for participants from the clinician's perspective.…”
Section: Associations Between Sdm Elements and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…There has not been adequate evidence to suggest significant impact on patients' decision making (Violette, Agoritsas et al 2015). However, patient participation was found to be increased in the patient population provided with decision aids, as well as the likelihood of patients choosing brachytherapy (Lin, Aaronson et al 2009, van Tol-Geerdink, Willem Leer et al 2013). …”
Section: Information Preferencementioning
confidence: 99%